Changing tidal hydrodynamics during different stages of eco-geomorphological development of a tidal marsh: A numerical modeling study. (15th March 2017) - Stark, J.; Meire, P.; Temmerman, S.
Abstract: The eco-geomorphological development of tidal marshes, from initially low-elevated bare tidal flats up to a high-elevated marsh and its typical network of channels and creeks, induces long-term changes in tidal hydrodynamics in a marsh, which will have feedback effects on the marsh development. We use a two-dimensional hydrodynamic model of the Saeftinghe marsh (Netherlands) to study tidal hydrodynamics, and tidal asymmetry in particular, for model scenarios with different input bathymetries and vegetation coverages that represent different stages of eco-geomorphological marsh development, from a low elevation stage with low vegetation coverage to a high and fully vegetated marsh platform. Tidal asymmetry is quantified along a 4 km marsh channel by (1) the difference in peak flood and peak ebb velocities, (2) the ratio between duration of the rising tide and the falling tide and (3) the time-integrated dimensionless bed shear stress during flood and ebb. Although spatial variations in tidal asymmetry are large and the different indicators for tidal asymmetry do not always respond similarly to eco-geomorphological changes, some general trends can be obtained. Flood-dominance prevails during the initial bare stage of a low-lying tidal flat. Vegetation establishment and platform expansion lead to marsh-scale flow concentration to the bare channels, causing an increase in tidal prism in the channels along with a less flood-dominant asymmetry of the horizontal tide. The decrease in flood-dominance continues as the platform grows vertically and the sediment-demand of the platform decreases. However, when the platform elevation gets sufficiently high in the tidal frame and part of the spring-neap cycle is confined to the channels, the discharge in the channels decreases and tidal asymmetry becomes more flood-dominant again, indicating an infilling of the marsh channels. Furthermore, model results suggest that hydro-morphodynamic feedbacks based on tidal prism to channel cross-sectional area relationships keep the marsh channels from filling in completely by enhancing ebb-dominance as long as the tidal volume and flow velocities remain sufficiently high. Overall, this study increases insight into the hydro-morphodynamic interactions between tidal flow and marsh geomorphology during various stages of eco-geomorphological development of marshes and marsh channels in particular.